The Mutiny of the Pseudonyms in the Kierkegaardian Authorship - Lopes, Paulo Henrique (Kierkegaard studies. Yearbook, 2020)
The essay emphasizes the unsolvable tension between activity and passivity implied in Kierkegaard’s reduplication as an author of authors. To characterize the different approaches to pseudonymity, I will use the term Halvbefaren [the inexperienced seaman] to refer to a reading that appeals only to Kierkegaard’s or to the pseudonyms’ authority over the authorship, and Helbefaren [the experienced seaman] to refer to another interpretation that recognizes that unsolvable tension between them. Recurring to the sailing metaphor implicit in these terms that appear in Climacus’ Postscript , I defend the thesis that the pseudonyms open the authorship from within, overcoming Kierkegaard as a usual author, as the only captain of the entire authorship. The mutiny performed by the pseudonyms cannot be resolved by simply transferring the authority to the pseudonyms themselves, and it creates a subjective space in the authorship so it becomes a matter of the experience of the reader.